Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berbasis Kurikulum Merdeka di Sekolah Menengah Islam - Tisna, Mohamad (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Islamic Religious Education and Ethics as a series of Islamic subjects are delivered both formally at school or informal and non-formally at home and in the community with materials taught from elementary school to tertiary level must respond well to this Independent Curriculum policy. Using the library research method, it was concluded that the Independent Curriculum version of Islamic Religious Education and Ethics Learning is designed to train students to have the ability to think critically, have creativity, have communication skills and make students have cooperation and be able to collaborate so that later students can have more mature thinking, wiser, more careful so that students are able to understand, develop and apply Islamic teachings in daily life.